(untitled) (Annual of the Faculty of Philosophy in Skopje, 2007)
The well-known French writer and philosopher, Albert Camus, in his ‘Myth of Sisyphus’ claims that absurd exists because reality does not satisfy our requests. In a way, this points to the fact that reality could satisfy these requests if it were different. The other well-known writer, Manuel Castells in his book, “The Information Age: Economy, Society and Culture - The Rise of the Network Society”, points to a dialectical interaction between technology and society: Technology does not determine society: it embodies it. But neither does society determinete technologycal inovation: it uses it. According to Castells, the present phase of capitalism has become possible because of developments in information technology. The introduction of innovations in the area of microelectronics, telecommunications, digital electronics, and network computing represent the rise of a new technological paradigm which becomes the basis of socio-economic relations. These new technologies effect pervasively all levels of production in different sectors as well as the whole of society. Unfortunately, technology became an end in itself. Of course, we are all aware that we need a certain changes to subdue technology, but I think it is now too late to change the course of technology. However, technology is frequently pictured as the only hope for a better future and the only means of making the world more humane. And that is the sort of statement that French philosopher Jacques Ellul calls the technological bluff. Technology is a discourse on techniques: therefore, the bluff lies not in the failure of techniques as such but in presenting them in a falsely optimistic light. The author formulated in 1954 two laws of technical progress: first, it is irreversible: second, it advances by a geometric progression. Thus, a computer revolution changes nothing in the nature of technical progress, although products are new. This progress is hampered not by internal mechanisms, but by maladaptation of the social body to it, since society is rooted in the past and constantly refers to it. On the other hand, technique is future oriented and discards as valueless everything that cannot be incorporated into the web of techniques. But, one of the features of the technical world is uncertainty. Technical progress does not know where it is going. This is why it is unpredictable. It always has both positive and negative effects, and they are inseparable; technical progress also creates more problems than solutions. This leads us to the observation that real technology and virtual technology are of different natures, if real and virtual are taken to refer to the degree to which mortality composes the experiential field of their operation. The first involves conflictual meaning and the second non-conflictual meaning (Le. the assumption that there is pure information which has a value per se). It could be argued that this is a false distinction, since all technology becomes real as it becomes past: the Gothic cathedral, the great iron structures of the nineteenth century and the super-computer are all the real solutions to virtual problems. The difference lies in the excess of means, which characterized those earlier technologies: the cathedral or the bridge employs more strength than is necessary for the weight to be borne, the technical means exceeding the effective end. The supplement is a supplement of the human imagination unsure as to the response of the material: the structure is a priori so threatened by mortality that excessive means must be used to guarantee its survival. In information technology, on the other hand, there is a convergence of means and ends. It uses the information it generates as its own material: it is the apotheosis of subjectivity projected into the domain of the material, which thereby becomes virtual (subjective- in-its elf).